2004
DOI: 10.1038/sj.npp.1300398
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genes Regulated by Memantine and MK-801 in Adult Rat Brain by cDNA Microarray Analysis

Abstract: In this study, we monitored gene expression profiles using cDNA microarrays after an acute systemic administration of the high affinity N-methyl-D-aspartate (NMDA) uncompetitive antagonist MK-801 (1 mg/kg; 4 h), and the clinically used moderate affinity antagonist memantine (25 mg/kg; 4 h) in adult rat brains. From a microarray containing 1090 known genes, 13 genes were regulated by both treatments of which 12 were upregulated and one was downregulated. In addition, 28 and 34 genes were regulated (X1.5-or p0.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 44 publications
3
22
0
Order By: Relevance
“…Therefore, it is reasonable to think that the amelioration of dopamine deficits by memantine in our study might rather be due to the observed BDNF upregulation than to the generally known NMDA antagonist action of memantine. In this line, a recent report on administration of memantine in adult rats, led to upregulation of several genes independent of the glutamatergic blockade, suggesting broader actions than previously realized (Marvanova et al, 2004). The trophic quality of memantine shown in this manuscript is supported by a paper published during the revision of our manuscript on the effects of a short-term treatment of HIV patients with memantine.…”
Section: Pharmacological Action Of Memantine F Meisner Et Alsupporting
confidence: 70%
“…Therefore, it is reasonable to think that the amelioration of dopamine deficits by memantine in our study might rather be due to the observed BDNF upregulation than to the generally known NMDA antagonist action of memantine. In this line, a recent report on administration of memantine in adult rats, led to upregulation of several genes independent of the glutamatergic blockade, suggesting broader actions than previously realized (Marvanova et al, 2004). The trophic quality of memantine shown in this manuscript is supported by a paper published during the revision of our manuscript on the effects of a short-term treatment of HIV patients with memantine.…”
Section: Pharmacological Action Of Memantine F Meisner Et Alsupporting
confidence: 70%
“…A two way analysis of variance (ANOVA) was used to detect genes with statistically significant expression levels between each Toxoplasma strain and their corresponding set of mock-infected cells. Due to the exploratory nature of the study and the fact that the brain normally shows small changes in gene expression (Marvanová et al 2004; Guiry et al 2010), genes were judged to be differentially expressed if their transcripts differed from that of controls with an ANOVA p < 0.01 and a fold change > 1.2 fold in either direction. Based on the differentially expressed gene list, a further group of genes coding for NNS was selected according to the KEGG PATHWAY database (hsa04080,!Neuroactive ligand-receptor interaction-Homo sapiens: http://www.genome.jp/kegg-bin/show_pathway?hsa04080).…”
Section: Methodsmentioning
confidence: 99%
“…A two-way analysis of variance (ANOVA) was used to detect genes with statistically significant expression levels between Toxoplasma strains and their corresponding sets of mock-infected cells. Due to the exploratory nature of the study and the fact that the brain normally shows small changes in gene expression (18,37), genes whose transcripts were judged to be differentially expressed, meaning they had to have an ANOVA P value of Յ0.01 and a change in expression of at least 1.2-fold in either direction, were selected as candidates for further functional analyses (54,58).…”
Section: Methodsmentioning
confidence: 99%